Corporate Governance, Ownership Structure, CSR, and Firm Performance: Empirical Evidence from Indonesian Mining Firms - Fakhri Maulidi; Sovi Ismawati Rahayu (Taxation and Public Finance, 2026)
This study examines the influence of the independent board of commissioners, managerial ownership structure, firm size, and corporate social responsibility (CSR) on the performance of mining firms listed on the Indonesia Stock Exchange during 2017–2021. The study is grounded in agency theory, which explains the relationship between principals and agents in achieving effective corporate governance and organizational performance. Previous studies have reported inconsistent findings regarding the effects of governance mechanisms, ownership structure, firm size, and CSR on firm performance, particularly in the mining sector, creating a research gap that motivates this study. Using a quantitative approach, this study employs secondary data obtained from annual reports and financial statements of 14 mining firms selected through purposive sampling. Multiple linear regression analysis was used to examine the relationships among variables. The findings indicate that firm size significantly influences firm performance, whereas the independent board of commissioners, managerial ownership structure, and CSR do not have significant effects. This study contributes to the corporate governance and performance literature by providing empirical evidence from the Indonesian mining sector. The results offer practical implications for management in enhancing asset efficiency, governance quality, and long-term business sustainability.